Biosynthesis of cryptic lipopolysaccharide glycoforms in Haemophilus influenzae involves a mechanism similar to that required for O-antigen synthesis. - Hood, D; Randle, G; Cox, A; Makepeace, K; Li, J; Schweda, E; Richards, J; Moxon, E (2004)
It is generally thought that mucosal bacterial pathogens of the genera Haemophilus, Neisseria, and Moraxella elaborate lipopolysaccharide (LPS) that is fundamentally different from that of enteric organisms that express O-specific polysaccharide side chains. Haemophilus influenzae elaborates short-chain LPS that has a role in the pathogenesis of H. influenzae infections. We show that the synthesis of LPS in this organism can no longer be as clearly distinguished from that in other gram-negative bacteria that express an O antigen. We provide evidence that a region of the H. influenzae genome, the hmg locus, is involved in the synthesis of glycoforms in which tetrasaccharide units are added en bloc, not stepwise, to the normal core glycoforms, similar to the biosynthesis of an O-antigen.